Intragenic and intergenic coaggregation of Candida albicans, Actinomyces naeslundii and Streptococcus mutans - Arzmi, Mohd Hafiz; Dashper, Stuart; McCullough, Michael (2013)
Objective: To determine the effect of intragenic and intergenic interaction to the coaggregation of C. albicans, A. naeslundii and S. mutans. Methods: 2-day old C. albicans strains and bacteria (A. naeslundii and S. mutans) were inoculated in RPMl-1640 and brain heart infusion broth, respectively. Following inoculation, the suspensions were incubated at 37 °C for 48 hours. Suspensions of C. albicans strains, A. naeslundii and S. mutans, after washing twice, were resuspended in coaggregation buffer to give total cell number of 106 cells/ml, 10 7 cells/ml and 108 cells/ml, respectively. The inocula were vortexed for 30 seconds and incubated at room temperature for an hour. The absorbance before and after incubation were recorded. lntergenic coaggregation were done according to the previous method by adding two or three species in 2 ml vial to give similar cell concentration as in the intragenic assay. The experiment was done in triplicate at two different occasions. Results: Significant intragenic coaggregation variation was observed between C. albicans strains (P<0.05) with four strains [ATCC 90234 (ALT3}, ATCC 18804 (ALT4), C. albicans serotype A (ALC1) and an oral cancer (OC) isolate 1 (ALC3)] categorized as ©ighrcoaggregation and two strains [ATCC MYA-2876 (AL T2) and C. albicans serotype B (ALC2)] showing ®>wrcoaggregation. Two further strains [ATCC 32354(ALT1) and OC isolate 2 (ALC4)] possessed intermediate coaggregation. A. naeslundii and S. mutans coaggregated with C. albicans to a much greater extent than they did intragenically. The bacteria also exhibited C. albicans intragenic coaggregation inhibition, with S. mutans inhibiting more than A. naes/undii in dualspecies interaction (P<0.05). Tri-species interaction further significantly decreased coaggregation from dual-species interaction (P<0.05). Conclusion: Coaggreation is strain dependant for C. albicans. lntergenic interaction increases coaggregation of bacteria, while intergenic coaggregation inhibits coaggregation of C. albicans.